Nutritional and Metabolic Factors, Ethanol and Cholesterol, Interact With Calcium-Dependent N-Methyl-D-Aspartate Receptor Inhibition by Tricyclic Antidepressants - Boikov, Sergei I.; Sibarov, Dmitry A.; Antonov, Sergei M. (Frontiers in Cellular Neuroscience, 2022)
It is known that overexpression of N-methyl-D-aspartate receptors (NMDARs) contributes to central sensitization and development of neuropathic pain. Tricyclic antidepressants (TCAs), amitriptyline (ATL), and desipramine (DES) exhibit analgetic anti-NMDAR activity and are commonly utilized for pain therapy. This property is determined by their ability to enhance the calcium-dependent desensitization (CDD) of NMDARs. Coincidently ethanol and cholesterol, the ubiquitous food supplements, also modulate NMDAR CDD. The convergence of the effects of these compounds on a similar calcium-dependent process allows to assume their interaction on NMDARs. Since there is no information on whether ethanol supplementation and cholesterol deficit interfere with TCA inhibition of NMDARs at a cellular level, here we investigated this issue. Whole-cell NMDA-activated currents were recorded in rat cortical neurons of primary cultures to study how the IC50 values for TCA inhibition of NMDARs are influenced by ethanol and cholesterol extraction from the plasma membrane with methyl-β-cyclodextrin. Ethanol at 0.03% did not reliably affect the steady-state NMDA-activated currents. At this threshold concentration ethanol, however, increased IC50s for ATL and DES abolishing their calcium-dependent inhibition of NMDARs but did not change IC50 for clomipramine, which is calcium-independent. Whereas the ethanol effects on ATL-induced NMDAR inhibition reached a maximum at 2 mM external [Ca2+], for DES the maximum was achieved already at 1 mM external [Ca2+], that correlates with the manifestation of the calcium-dependent inhibition of NMDARs by these agents. Cholesterol depletion also increased IC50s for both ATL and DES abolishing the calcium-dependent inhibition of NMDARs. The restitution of cholesterol in the plasma membrane reversed the ATL IC50 back to the low values, by a restoration of calcium-dependence of ATL. These observations are consistent with the explanation that either 0.03% ethanol or cholesterol extraction may interrupt some intermediate step of CDD transduction or augment NMDAR CDD to the maximal level so that ATL and DES could not further enhance CDD. It is likely that anti-NMDAR action of ATL and DES against neuropathic pain could demonstrate peculiarities in therapeutic profiles during cholesterol decline in aging or medical treatments and ethanol supplementations even in quantities that are insufficient to cause the symptoms of intoxication.